Effect of Solid State Fermentation (SSF) Biomass Supplementation on Nutrient Intake, Growth Performance and Cost of Feeding in Crossbred Heifers - Chaudhari, Fenil N; Shekh, Makbul A; Chaudhari, Hitesh H; Darji, Vijay B (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
This study was aimed to evaluate the effect of solid state fermentation (SSF) biomass supplementation (@ 3%) on nutrient intake, growth performance and cost of feeding in crossbred heifers. Fifteen crossbred heifers were randomly divided into three groups each of five animals based on body weight, and were individually fed for 98 days. The heifers were fed jawar hay and wheat straw based total mixed ration (TMR) without SSF (T1, control), TMR with 3% SSF biomass (T2) and TMR having 10% reduction in protein and energy with 3% SSF biomass (T3). The results showed that the average dry matter intake (DMI) remained similar among the groups. However, the average crude protein intake (CPI) and total digestible nutrient intake (TDNI) differed significantly in T1 and T2 groups as compared to T3. The average daily body weight gain was significantly increased (p<0.05) in SSF fed group T2 than control group. The feed cost in terms of Rs./kg b. wt. gain was significantly (p<0.05) lower in T2 group as compared to control T1 group.